1989
DOI: 10.1021/la00088a003
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption of butadiene on molybdenum (100) below room temperature

Abstract: Ultraviolet photoelectron spectroscopy indicates that butadiene adsorbs molecularly onto Mo(100) at 120-150 K. The occupied molecular orbitals are only minimally perturbed on adsorption, and work function measurements indicate that bonding to the surface is by electron donation from the metal to the adsorbed butadiene. Both near-edge X-ray absorption fine-structure measurements and angle-resolved photoelectron spectroscopy indicate that the molecular plane of butadiene is oriented at ~40°to the metal surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We suggest that this may correspond to the formation of a metallacyclic species, perhaps CH(Pt)CHdCHCH(Pt). Similar intermediates have been isolated on other metals starting from butadiene 61 and are also known in the organometallic literature. 16 Both the selective hydrogenation of 1,3-butadiene and the hydrogenation and isomerization of polyunsaturated olefins are central catalytic processes in the oil reforming and food industries.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We suggest that this may correspond to the formation of a metallacyclic species, perhaps CH(Pt)CHdCHCH(Pt). Similar intermediates have been isolated on other metals starting from butadiene 61 and are also known in the organometallic literature. 16 Both the selective hydrogenation of 1,3-butadiene and the hydrogenation and isomerization of polyunsaturated olefins are central catalytic processes in the oil reforming and food industries.…”
Section: Discussionmentioning
confidence: 58%
“…We suggest that this may correspond to the formation of a metallacyclic species, perhaps CH(Pt)CHCHCH(Pt). Similar intermediates have been isolated on other metals starting from butadiene and are also known in the organometallic literature …”
Section: Discussionmentioning
confidence: 61%
“…The difference in the dehydrogenation path for the metals can be attributed to the difference in the chemisorbed state of molecules. Our previous studies revealed that 1,3-butadiene and butene isomers are adsorbed on Pd(110) with the π character, ,, while they are σ bonded on Pt, Ru, and Mo surfaces. ,, The metal−molecule interaction is much weaker for the π-bonded system than for the σ-bonded system. In fact, upon 1,3-butadiene adsorption on Pt(111) and Ru(0001), , 1,4-di-σ-bonding species is formed at 210 K followed by the decomposition to a (CH) 4 metallacycle at 260 K and to a CCHCHC metallacycle at 400 K. Compared with this thermal activity of σ-bonded 1,3-butadiene, the π-bonded 1,3-butadiene remains intact on Pd(110) at a much higher temperature up to 350 K. The higher thermal stability of the π-bonded 1,3-butadiene until decomposition would allow itself to be hydrogenated by the thermally activated hydrogen adatoms.…”
Section: Resultsmentioning
confidence: 99%
“…This is a fairly common reaction on transition metal surfaces, and appears to require an initial 1,2-H shift in the adsorbed olefin to produce an unstable alkylidene intermediate [163]. In a third example, adsorbed butadiene sometimes isomerizes to a species resembling 2-butene, perhaps an unsaturated metallacyclopentene [164]. However, it is not clear if in that case the double bond migration occurs via a dehydrogenation/rehydrogenation sequence or directly by hydrogen transfer.…”
Section: Other Elementary Stepsmentioning
confidence: 99%